Genome-wide characterization of terpene synthase genes in Ginkgo biloba and their regulatory role in terpene trilactones biosynthesis - Ang Xu; Chenglin Luo; Chunxia Chen; Yumeng Gao; Wenjing Qin; Qi Wang; Lisha Shi; Xiaoming Yang; Meiling Ming; Fuliang Cao; Fangfang Fu (Plant Science, 2026)

Mild hydrolysis and upgrading utilization of waste PET: Preparation of regenerated TPA and MOF materials and study of their adsorption performance - Wei Lin; Meiling Zhang; Shun Zhang; Sheng Shi; Zeyu Wang; Chengyong Gao; Shuhua Wang; Enbin Zhu (Sustainable Chemistry and Pharmacy, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Dissolved organic matter dynamics and antibiotic resistance gene attenuation during composting: Characteristics and interrelationships - Dongfang Shi; Meiling Shi; Shengnan Zhang; Pengyan Zhang; Xiaoyan Qian; Yongjun You; Chong Liu; Fayong Li (Journal of Environmental Chemical Engineering, 2026)

Design and Performance Evaluation of Amino Acid-Decorated UiO-66-NH2/Pebax Mixed Matrix Membranes for Efficient CO2 Separation - Xiaochun Jing; Wei Zhao; Pengzhi Bei; Hongjing Liu; Yan Dai; Xu Zhao; Chengpeng Zhang; Meiling Shi; Ying Zhang (Water, Air, & Soil Pollution, 2026)

Decoupling predictors of arbuscular mycorrhizal fungal α- and β-diversity: Plant phylogeny versus functional traits in an alpine artificial grassland of Three-River Source Region - Guoxi Shi; Yingli Ma; Ning Wu; Meiling Guo; Xinchuang Wang; Yongjun Liu; Huyuan Feng; Huakun Zhou; Buqing Yao (Applied Soil Ecology, 2026)

Recycling and valorization of waste colored polyester through a zero-waste approach - Yazhou Wang; Shuhua Wang; Ji Lan; Shaoping Jiang; Yufang Weng; Sheng Shi; Chengyong Gao; Meiling Zhang (Waste Management, 2026)

Multifunctional metallized basalt/PA6 composites: EMI shielding, joule heating, and tunable rigidity - Jiajun Du; Hao Shi; Xin Wang; Meiling Xiang; Jing Zhang (Chemical Engineering Journal, 2026)

Study on ball milling driven solvent extraction – Ozone oxidation decolorization of waste printed polyester fabrics - Xiao Li; Chengyong Gao; Wansi Li; Sheng Shi; Enbin Zhu; Meiling Zhang; Shuhua Wang (Process Safety and Environmental Protection, 2026)

Effects of humic acid and microbial agents on contaminated manure composting: Heavy metal passivation, gaseous emission mitigation and microbial community response - Meiling Shi; Xiaojuan Wang; Jie Gu; Xuefei Hu; Fayong Li; Yongjun You; Pengyan Zhang (Process Safety and Environmental Protection, 2026)

Optimal information transmission in a non-Markovian auto-regulatory gene expression system - Zihao Wang; Meiling Chen; Zhenquan Zhang; Xiyan Yang; Tianshou Zhou; Changhong Shi; Jiajun Zhang (BioSystems, 2026)

Effects of long-term plastic film mulching on microplastic and phthalate esters pollution in salt-affected soils: Microbial community shifts and enrichment of putative degraders - Jiabin Li; Yunfeng Pu; Yongjun You; Shengnan Zhang; Xiaoyan Qian; Meiling Shi; Guocai Ma; Chong Liu; Kamel M. Eltohamy; Fayong Li (Journal of Hazardous Materials, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Impact of environmental salinity on the MAPK-NFAT5 pathway in Trachemys scripta elegans and its role in osmoregulaton - Xin Niu; Yingnan Lu; Yue Yuan; Jiao Li; Yunjuan Xiao; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Ferrihydrite sulfidation transformation and coupled As(V) and Cd(II) mobilization under anoxic conditions - Xiaoming Zhao; Xu Ma; Yuyin Ma; Zidan Yuan; Shaofeng Wang; Yuanming Pan; Meiling Shi; Jinru Lin (Journal of Hazardous Materials, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Recycling of waste denim: A stepwise utilisation strategy for clean decolourisation, opening and degradation - Zhao Li; Meiling Zhang; Fei Li; Sheng Shi; Shuhua Wang; Chengyong Gao; Yiming Li (Waste Management, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Unraveling the trisubstrate-triproduct reaction mechanisms of wine grape VvCYP76F14 to improve wine bouquet - Zhizhong Song; Meiling Tang; Huilin Xiao; Houhua Xu; Matthew Shi; Adeeba Dark; Zhenqiang Xie; Bin Peng (Food Chemistry, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Characteristics, sources, and health risks of fine particulate matter in Wuhan subway, China - Ji-Liang Lü; Qing Han; Zhen Wang; Min Tao; Xun Hu; Meiling Cao; Qingzhu Huang; Mengdie Shi; Zhenyu He; Xiaohu Zhao (Science of The Total Environment, 2025)

Keystone taxa drive the synchronous production of methane and refractory dissolved organic matter in inland waters - Xinjie Shi; Wanzhu Li; Baoli Wang; Na Liu; Xia Liang; Meiling Yang; Cong-Qiang Liu (Water Research, 2025)

A lightweight fine-grained pelagic fish recognition algorithm based on object detection - Weiyu Ren; Dongfan Shi; Yifan Chen; Liming Song; Qingsong Hu; Meiling Wang (Aquaculture International, 2025)

Ultrastable Ti@Ir core-shell catalyst with low iridium loading for water electrolysis at industrial-level current density - Jiahao Yang; Zhaoping Shi; Yibo Wang; Hongxiang Wu; Jing Ni; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (Chemical Engineering Journal, 2025)

Evaluation of the gully erosion susceptibility by using UAV and hybrid models based on machine learning - Qian Wang; Bohui Tang; Kailin Wang; Jiannan Shi; Meiling Li (Soil and Tillage Research, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Microbial regulation on refractory dissolved organic matter in inland waters - Wanzhu Li; Baoli Wang; Na Liu; Xinjie Shi; Meiling Yang; Cong-Qiang Liu (Water Research, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

Seasonal changes in hepatic lipid metabolism and apoptosis in Chinese soft-shelled turtle (Pelodiscus sinensis) - Xiaoqi Ai; Rui Lin; Zeeshan Ali; Qingjun Zhu; Li Ding; Haitao Shi; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Stepwise degradation of organic matters driven by microbial interactions in China΄s coastal wetlands: Evidence from carbon isotope analysis - Meiling Yang; Na Liu; Baoli Wang; Yajun Li; Wanzhu Li; Xinjie Shi; Xinrui Yue; Cong-Qiang Liu (Water Research, 2024)

Metagenomic binning analyses of swine manure composting reveal mechanism of nitrogen cycle amendment using kaolin - Huakang Li; Zixuan Zhao; Meiling Shi; Bin Luo; Guangdong Wang; Xiaojuan Wang; Jie Gu; Zilin Song; Yifan Sun; Li Zhang; Jia Wang (Bioresource Technology, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

One-step synthesis of color-tunable carbon dots-based organic long persistent luminescence materials - Yujie Di; Weifeng Liu; Shuhao Shi; Tao Wu; Meiling Wang; Xuguang Liu (Chemical Engineering Journal, 2024)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

Aerogel-hydrogel biphase gels based on physically crosslinked β-lactoglobulin fibrils/polyvinyl alcohol for skin wound dressings: In vitro and in vivo characterization - Min Gong; Huanhuan Shi; Zuquan Hu; Fang Wang; Meiling Dong; Ronghua Lei; Zhu Zeng; Yun Wang; Jin Chen (Chemical Engineering Journal, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Profiles and key drivers of bacteria/phage co-mediated antibiotic resistance genes during swine manure composting amended with humic acid - Meiling Shi; Zixuan Zhao; Xiaojuan Wang; Huakang Li; Jie Gu; Zilin Song; Ting Hu; Yifan Sun; Han Wang (Bioresource Technology, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Intermetallic niobium boride toward efficient adsorption and catalysis of polysulfides in Lithium-Sulfur batteries - Li He; Yingjie Cheng; Qiuju Li; Hainan Zhao; Meiling Wang; Xuejian Shi; Xiaoxin Zou; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

Effect of ammonia stress on AMPK regulating-carbohydrate and lipid metabolism in Chinese striped-neck turtle (Mauremys sinensis) - Ijaz Khan; Yingnan Lu; Na Li; Haitao Shi; Li Ding; Meiling Hong; Zhenhua Fang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Isoliquiritigenin attenuates pathological cardiac hypertrophy via regulating AMPKα in vivo and in vitro - Meiling Gao; Qiang Cai; Haichao Si; Si Shi; Huixia Wei; Miaomiao Lv; Xiaofan Wang; Tieli Dong (Journal of Molecular Histology, 2022)

Comparative transcriptome analysis of global effect of ddh and lysE deletion on 4-hydroxyisoleucine production in Corynebacterium glutamicum - Rui Chen; Youhe Xiang; Xinping Yu; Meiling Zhang; Feng Shi (Systems Microbiology and Biomanufacturing, 2022)

Implications of spatial priority areas for hydrological ecosystem services through coupling hydrology model and Zonation model under different economic costs of water utilizations in northernmost of Japan - Min Fan; Manjiang Shi; Yunfeng Liu; Wen Chen; Yue Deng; Meiling Wang (Mitigation and Adaptation Strategies for Global Change, 2022)

Genetic architecture of fruit size and shape variation in cucurbits: a comparative perspective - Yupeng Pan; Yuhui Wang; Cecilia McGregor; Shi Liu; Feishi Luan; Meiling Gao; Yiqun Weng (Theoretical and Applied Genetics, 2020)

OsEXPA10 mediates the balance between growth and resistance to biotic stress in rice - Jiang Tan; Meiling Wang; Zhenying Shi; Xuexia Miao (Plant Cell Reports, 2018)

Steroid 5-alpha-reductase type 2 (SRD5A2) V89L and A49T polymorphisms and sporadic prostate cancer risk: a meta-analysis - Qiaoxin Li; Yao Zhu; Jing He; Mengyun Wang; Meiling Zhu; Tingyan Shi; Lixin Qiu; Dingwei Ye; Qingyi Wei (Molecular Biology Reports, 2013)

LIM-homeobox gene Lhx8 promote the differentiation of hippocampal newborn neurons into cholinergic neurons in vitro - Peipei Zhu; Haoming Li; Guohua Jin; Meiling Tian; Xuefeng Tan; Jinhong Shi; Linqing Zou; Jianbing Qin (In Vitro Cellular & Developmental Biology - Animal, 2013)

Lhx8 promote differentiation of hippocampal neural stem/progenitor cells into cholinergic neurons in vitro - Jinhong Shi; Haoming Li; Guohua Jin; Peipei Zhu; Meiling Tian; Jianbing Qin; Xuefeng Tan; Shuqing Zhao; Fuyu Wang; Yurong Hua; Yong Xiao (In Vitro Cellular & Developmental Biology - Animal, 2012)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)